The Analisis Perancangan Aplikasi Sistem Informasi Akuntansi Persediaan Menggunakan Software Microsoft Access 2019 (Studi Kasus Pada Expose Coffee - Subang) - Rangga Rif'aa Ariibah; Rendra Trisyanto Surya (Indonesian Accounting Literacy Journal, 2023)
Expose Coffee is a service-based company that serves various types of food and beverages to its customers, much like a typical cafe. Expose Coffee conducts numerous transactions on a daily basis. However, the company still maintains manual inventory records, resulting in inaccurate inventory values. Based on this issue, the author intends to design an inventory accounting information system application to assist the company in its operational activities. This research is a qualitative descriptive study with a case study approach. The data analysis technique employed by the author to design the application is the Systems Development Life Cycle (SDLC) method, specifically the waterfall model. The application will be designed using Microsoft Access 2019 software, with features tailored to the company's needs. It is expected that this application will address the existing challenges by generating information such as inventory data, inventory cards, and inventory transaction reports.